On a Max-Type Difference Inequality and Its Applications - Stevo Stević; Bratislav D. Iričanin (Discrete Dynamics in Nature and Society)
We prove a useful max-type difference inequality which can be applied in studying of some max-type difference equations and give an application of it in a recent problem from the research area. We also give a representation of solutions of the difference equation 𝑥𝑛=max{𝑥𝑎1𝑛−1,…,𝑥𝑎𝑘𝑛−𝑘}.